Long-term serological monitoring of Leishmania infantum in European wild rabbits (Oryctolagus cuniculus) in Mediterranean ecosystems of southern Spain - Jesús Barbero-Moyano; Moisés Gonzálvez; David Cano-Terriza; Saúl Jiménez-Ruiz; Sabrina Castro-Scholten; Débora Jiménez-Martín; Félix Gómez-Guillamón; Leonor Camacho-Sillero; Inmaculada Moreno; Mercedes Domínguez; Jonás Carmona-Pírez; Carlos Rouco; et al. (Preventive Veterinary Medicine, 2026)

Definition of regional background values of trace element in soils of Castilla-La Mancha region, Spain - Iker Martínez-del-Pozo; Mónica Celina Gómez-Pachón; Sofía Rivera; Inmaculada Ferri-Moreno; Mari Luz García-Lorenzo; Saturnino Lorenzo; José Ignacio Barquero-Peralbo; Xabier Arroyo; Pablo Higueras; José María Esbrí (Applied Geochemistry, 2026)

Nature-based solutions for nutrient and emerging contaminant reduction in a Mediterranean Ramsar wetland - Emilio Moreno; María Gómez-Pozuelos; Francisco Guerrero; Cristina Postigo; África Lupión; José María Conde-Porcuna; Inmaculada de Vicente (Environmental Geochemistry and Health, 2026)
Constructed wetlands are widely recognized as nature-based solutions for improving water quality in systems receiving treated wastewater. However, their effectiveness depends primarily on hydrological connectivity, contaminant properties, and hydraulic residence time. In Mediterranean wetlands, where strong hydrological variability and seasonal water scarcity influence water quality dynamics, understanding attenuation processes under contrasting water-circulation scenarios is relevant for protecting sensitive downstream ecosystems. This study assessed the capacity of a semi-natural pond system i.e., a series of interconnected shallow ponds comprising both natural and managed water bodies that receive treated wastewater while retaining natural wetland characteristics, located upstream of the Fuente de Piedra Ramsar wetland main basin (southern Spain) to reduce nutrients and emerging contaminants under contrasting water-circulation scenarios. Across 26 sampling events, substantial reductions were observed when treated wastewater flowed through the semi-natural pond system before reaching the main wetland basin, including decreases of 75% in total nitrogen. Marked attenuation was detected for emerging contaminants with shorter environmental half-lives, such as trimethoprim, naproxen, caffeine and selected triazine metabolites showed removals exceeding 70–90%, whereas more persistent substances, including carbamazepine and gemfibrozil, exhibited limited reduction. In contrast, negligible changes occurred during a temporary bypass configuration put in place for restoration works, in which treated wastewater avoided most of the semi-natural ponds before reaching the main wetland basin. Dry-season conditions enhanced contaminant attenuation, largely reflecting lower flows and extended hydraulic residence times. Cumulative ecotoxicological risk, estimated using risk quotients (RQ sample ) based on measured environmental concentrations and the lowest predicted no-effect concentrations for freshwater organisms, declined downstream under the regular flow pathway, particularly for pesticides, but moderate risk persisted under the bypass scenario. Overall, the semi-natural pond system demonstrates a strong but hydrologically dependent capacity to mitigate nutrient and emerging contaminant loads entering a Mediterranean Ramsar wetland. Nevertheless, elevated phosphorus concentrations and the persistence of certain emerging contaminants highlight the limitations of natural attenuation alone and support the integration of complementary management and treatment strategies to ensure long-term ecosystem protection.

Portable X-ray fluorescence (pXRF) application to the determination of major and trace elements in large soil datasets for geochemical background assessment - Iker Martínez-del-Pozo; Mónica Celina Gómez-Pachón; Inmaculada Ferri-Moreno; Mari Luz García-Lorenzo; Saturnino Lorenzo; José Ignacio Barquero-Peralbo; Xabier Arroyo; Pablo Higueras; José María Esbrí (Journal of Geochemical Exploration, 2026)

Ecotoxicity assessment of primary producers in metal mining areas: biological indicators for ecosystem restoration - Inmaculada Ferri-Moreno; Iker Martínez-del-Pozo; José María Esbrí; Mari Luz García-Lorenzo; Oscar Andreu-Sánchez (Environmental Research, 2026)

Deployment of a Dense Seismic Network on La Palma Island (2023-2024) for High-Resolution Imaging of the Velocity Structure Using Passive Seismic Methods - Javier Tortosa; Javier Almendros; Enrique Carmona; José Benito Martín; Janire Prudencio; Joan Antoni Parera-Portell; Rafael Abella; Carlos Araque-Pérez; José Morales; Pablo Rey-Devesa; Benjamin Heit; Xiaohui Yuan; et al. (Surveys in Geophysics, 2026)
We present the IMAGMASEIS project, a large-N seismic experiment carried out on La Palma (Canary Islands, Spain) between 2023 and 2024, aimed at high-resolution imaging of the crustal and upper mantle structure using passive seismic methods. The project involved the deployment of 235 temporary broadband and short-period seismic stations, supplementing 21 permanent stations, thus creating the densest seismic network ever installed on the island. The main goal is to characterise the magmatic plumbing system beneath Cumbre Vieja volcano, identify magma accumulation zones, and investigate structural changes related to the 2021 Tajogaite eruption. We describe the experimental design, network configuration, instrumentation, deployment strategies, and challenges encountered, including difficult terrain and logistical constraints. Preliminary results demonstrate the potential of the dataset for ambient noise tomography, receiver function analysis, and local earthquake studies. IMAGMASEIS provides a valuable resource for understanding volcanic and tectonic processes in oceanic island settings and serves as a model for cost-effective, high-density seismic deployments in similar environments.

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Serosurvey of Leishmania infantum in equids in different European countries - Jesús Barbero-Moyano; David Cano-Terriza; Moisés Gonzálvez; Inmaculada Moreno; Eduard Jose-Cunilleras; Francesco Buono; Vincenzo Veneziano; Eduardo Alguacil; Jesús García; Fabrizia Veronesi; María A. Risalde; Ignacio García-Bocanegra (Preventive Veterinary Medicine, 2025)

A new model to estimate daytime net surface radiation under all sky conditions - Inmaculada Foyo-Moreno; Ismael L. Lozano; Inmaculada Alados; Juan Luis Guerrero-Rascado (Atmospheric Research, 2025)

Immunological mechanisms involved in the protection against development of pulmonary tuberculosis in naturally infected goats - Irene Agulló-Ros; Rita Vaz-Rodrigues; Mercedes Domínguez; Álvaro Roy; Javier Ortega; Inmaculada Moreno; Javier Bezos; Lucas Domínguez; Isabel G. Fernández de Mera; María A. Risalde (Veterinary Microbiology, 2025)

Monitoring of Leishmania infantum exposure in the Iberian lynx (Lynx pardinus) - Jesús Barbero-Moyano; Javier Caballero-Gómez; Moisés Gonzálvez; Remigio Martínez; Inmaculada Moreno; Eduardo Berriatua; Marta Sánchez-Sánchez; Jorge Paniagua; Isabel Fernández-Veron; María Teresa del Rey-Wamba; Elena Crespo; Juan I. Montoya-Oliver; et al. (Preventive Veterinary Medicine, 2025)

Monitoring of Leishmania infantum in captive non-human primates in Spain - Jesús Barbero-Moyano; Remigio Martínez; Moisés Gonzálvez; Inmaculada Moreno; Adrián Beato-Benítez; David Cano-Terriza; Andrea Carretero; Rocío Canales-Merino; Andrea Ferreiro-Prado; Juan J. Garrido; María A. Risalde; Ignacio García-Bocanegra (Research in Veterinary Science, 2024)

Epidemiological surveillance of Leishmania infantum in wild lagomorphs in Spanish Mediterranean ecosystems - Jesús Barbero-Moyano; Sabrina Castro-Scholten; Moisés Gonzálvez; Inmaculada Moreno; Mercedes Domínguez; David Cano-Terriza; Débora Jiménez-Martín; Leonor Camacho-Sillero; Remigio Martínez; Ignacio García-Bocanegra (Preventive Veterinary Medicine, 2024)

Mycobacterium tuberculosis complex in domestic goats in Southern Spain - Débora Jiménez-Martín; Ignacio García-Bocanegra; María A. Risalde; Sebastián Napp; Mercedes Domínguez; Beatriz Romero; Inmaculada Moreno; Remigio Martínez; David Cano-Terriza (Preventive Veterinary Medicine, 2024)

Analysis of the solar radiation/atmosphere interaction at a Mediterranean site: The role of clouds - Ismael L. Lozano; Inmaculada Alados; Inmaculada Foyo-Moreno (Atmospheric Research, 2023)

Oral immunization with heat-inactivated Mycobacterium bovis reduces local parasite dissemination and hepatic granuloma development in mice infected with Leishmania amazonensis - Elisa Ferreras-Colino; Inmaculada Moreno; Christian Gortázar; Iker Sevilla; Irene Agulló-Ros; Lucas Domínguez; Ramón Juste; Maria A. Risalde; Mercedes Domínguez (Research in Veterinary Science, 2023)

A new method to estimate aerosol radiative forcing on photosynthetically active radiation - Inmaculada Foyo-Moreno; Ismael L. Lozano; Inmaculada Alados; Juan Luis Guerrero-Rascado (Atmospheric Research, 2023)

Amino acids profile of 56 species of microalgae reveals that free amino acids allow to distinguish between phylogenetic groups - Antonio León-Vaz; Inmaculada Giráldez; Ignacio Moreno-Garrido; João Varela; Javier Vigara; Rosa León; José Pedro Cañavate (Algal Research, 2023)

Seroepidemiology of tuberculosis in sheep in southern Spain - Débora Jiménez-Martín; David Cano-Terriza; María A. Risalde; Sebastián Napp; Julio Álvarez; Manuel Fernández-Morente; Vicente Fernández-Molera; Inmaculada Moreno; José A. Infantes-Lorenzo; Ignacio García-Bocanegra (Preventive Veterinary Medicine, 2023)

Therapeutic Assay with the Non-toxic C-Terminal Fragment of Tetanus Toxin (TTC) in Transgenic Murine Models of Prion Disease - Marina Betancor; Laura Moreno-Martínez; Óscar López-Pérez; Alicia Otero; Adelaida Hernaiz; Tomás Barrio; Juan José Badiola; Rosario Osta; Rosa Bolea; Inmaculada Martín-Burriel (Molecular Neurobiology, 2021)
The non-toxic C-terminal fragment of the tetanus toxin (TTC) has been described as a neuroprotective molecule since it binds to Trk receptors and activates Trk-dependent signaling, activating neuronal survival pathways and inhibiting apoptosis. Previous in vivo studies have demonstrated the ability of this molecule to increase mice survival, inhibit apoptosis and regulate autophagy in murine models of neurodegenerative diseases such as amyotrophic lateral sclerosis and spinal muscular atrophy. Prion diseases are fatal neurodegenerative disorders in which the main pathogenic event is the conversion of the cellular prion protein (PrP C ) into an abnormal and misfolded isoform known as PrP Sc . These diseases share different pathological features with other neurodegenerative diseases, such as amyotrophic lateral sclerosis, Parkinson’s disease or Alzheimer’s disease. Hitherto, there are no effective therapies to treat prion diseases. Here, we present a pilot study to test the therapeutic potential of TTC to treat prion diseases. C57BL6 wild-type mice and the transgenic mice Tg338, which overexpress PrP C , were intracerebrally inoculated with scrapie prions and then subjected to a treatment consisting of repeated intramuscular injections of TTC. Our results indicate that TTC displays neuroprotective effects in the murine models of prion disease reducing apoptosis, regulating autophagy and therefore increasing neuronal survival, although TTC did not increase survival time in these models.

Human motion capture for movement limitation analysis using an RGB-D camera in spondyloarthritis: a validation study - Manuel Trinidad-Fernández; Antonio Cuesta-Vargas; Peter Vaes; David Beckwée; Francisco-Ángel Moreno; Javier González-Jiménez; Antonio Fernández-Nebro; Sara Manrique-Arija; Inmaculada Ureña-Garnica; Manuel González-Sánchez (Medical & Biological Engineering & Computing, 2021)
A human motion capture system using an RGB-D camera could be a good option to understand the trunk limitations in spondyloarthritis. The aim of this study is to validate a human motion capture system using an RGB-D camera to analyse trunk movement limitations in spondyloarthritis patients. Cross-sectional study was performed where spondyloarthritis patients were diagnosed with a rheumatologist. The RGB-D camera analysed the kinematics of each participant during seven functional tasks based on rheumatologic assessment. The OpenNI2 library collected the depth data, the NiTE2 middleware detected a virtual skeleton and the MRPT library recorded the trunk positions. The gold standard was registered using an inertial measurement unit. The outcome variables were angular displacement, angular velocity and lineal acceleration of the trunk. Criterion validity and the reliability were calculated. Seventeen subjects (54.35 (11.75) years) were measured. The Bending task obtained moderate results in validity (r = 0.55–0.62) and successful results in reliability (ICC = 0.80–0.88) and validity and reliability of angular kinematic results in Chair task were moderate and (r = 0.60–0.74, ICC = 0.61–0.72). The kinematic results in Timed Up and Go test were less consistent. The RGB-D camera was documented to be a reliable tool to assess the movement limitations in spondyloarthritis depending on the functional tasks: Bending task. Chair task needs further research and the TUG analysis was not validated. Graphical abstract Comparation of both systems, required software for camera analysis, outcomes and final results of validity and reliability of each test.

Genotype, environment and their interaction effects on olive tree flowering phenology and flower quality - Jose F. Navas-Lopez; Lorenzo León; Hava F. Rapoport; Inmaculada Moreno-Alías; Ignacio J. Lorite; Raúl de la Rosa (Euphytica, 2019)

Early life stage bottlenecks of carnivorous molluscs under captivity: a challenge for their farming and contribution to seafood production - Iker Uriarte; Marcela Astorga; Juan Carlos Navarro; María Teresa Viana; Carlos Rosas; Carlos Molinet; Jorge Hernández; Jorge Navarro; Ignacio Moreno‐Villoslada; Rodolfo Amthauer; Gudrun Kausel; Jaime Figueroa; et al. (Reviews in Aquaculture, 2019)
This work brings together the view of different specialists in the areas of larviculture, physiology, ecology, nutrition and animal health, regarding how to deal with the aquaculture farming of species with complex life cycles in a multidisciplinary way, using as models the octopus and the muricid C. concholepas , with the aim of reducing the gap between the experimental and the industrial culture of species that are relevant for the diversification of aquaculture, particularly in Chile. Although these species are similar in their difficulty to reach the terminal planktonic phase prior to juvenile, they differ in the bottlenecks they have to overcome to reach it. Relevant aspects of study to achieve juvenile production from early life stages rearing, whether for repopulation or for ongrowing, are as follows: (i) Replacement or supplementation of live diets with inert diets to achieve significant survival values over the first stages of life. (ii) Physiological approaches to establish cultivation conditions evaluating the individual responses to several rearing conditions, specially the interaction between temperature, dissolved oxygen and acidity. Studies of urgent character due to the global warming scenario. (iii) Genomic studies associated with the effect of ontogenetic development, environment, health and nutrition on gene expression to understand, in an integrated way, the key processes for the development and growth of immature stages. (iv) Studies on the control of reproduction, the quality control of the ova, the genetic structure of reproductive populations and the characterization of diseases are also necessary to achieve efficient hatchery technologies.

Coastal lateral spreading in the world heritage site of the Tramuntana Range (Majorca, Spain). The use of PSInSAR monitoring to identify vulnerability - Rosa María Mateos; Pablo Ezquerro; Jose Miguel Azañón; Bernadí Gelabert; Gerardo Herrera; Jose Antonio Fernández-Merodo; Daniele Spizzichino; Roberto Sarro; Inmaculada García-Moreno; Marta Béjar-Pizarro (Landslides, 2018)

Spectral analysis of climate cycles to predict rainfall induced landslides in the western Mediterranean (Majorca, Spain) - Juan Antonio Luque-Espinar; Rosa María Mateos; Inmaculada García-Moreno; Eulogio Pardo-Igúzquiza; Gerardo Herrera (Natural Hazards, 2017)

Calibration and validation of rockfall modelling at regional scale: application along a roadway in Mallorca (Spain) and organization of its management - Rosa María Mateos; Inmaculada García-Moreno; Paola Reichenbach; Gerardo Herrera; Roberto Sarro; Joan Rius; Raúl Aguiló; Federica Fiorucci (Landslides, 2016)

The Son Poc rockfall (Mallorca, Spain) on the 6th of March 2013: 3D simulation - Roberto Sarro; Rosa María Mateos; Inmaculada García-Moreno; Gerardo Herrera; Paola Reichenbach; Luís Laín; Carlos Paredes (Landslides, 2014)

Genetic variability and evolution of broad bean wilt virus 1: role of recombination, selection and gene flow - Inmaculada Ferriol; Rosa M. Ferrer; Marisol Luis-Arteaga; José Guerri; Pedro Moreno; Luis Rubio (Archives of Virology, 2014)

Identification and characterization of resistance to rust (Uromyces ciceris-arietini (Grognot) Jacz. & Boyd) in a germplasm collection of Cicer spp. - Josefina C. Sillero; Inmaculada Moreno-Alías; Diego Rubiales (Euphytica, 2012)

Freeze–thaw cycles and rainfall as triggering factors of mass movements in a warm Mediterranean region: the case of the Tramuntana Range (Majorca, Spain) - Rosa María Mateos; Inmaculada García-Moreno; Jose Miguel Azañón (Landslides, 2012)

Genetic variation and evolutionary analysis of broad bean wilt virus 2 - Rosa M. Ferrer; Inmaculada Ferriol; Pedro Moreno; José Guerri; Luis Rubio (Archives of Virology, 2011)

Phenological records as a complement to aerobiological data - Rafael Tormo; Inmaculada Silva; Ángela Gonzalo; Alfonsa Moreno; Remedios Pérez; Santiago Fernández (International Journal of Biometeorology, 2011)

MHC class II DRB1 gene polymorphism in the pathogenesis of Maedi–Visna and pulmonary adenocarcinoma viral diseases in sheep - Amaia Larruskain; Esmeralda Minguijón; Koldo García-Etxebarria; Bernardino Moreno; Inmaculada Arostegui; Ramón A. Juste; Begoña M. Jugo (Immunogenetics, 2010)

Morphological and anatomical evaluation of adult and juvenile leaves of olive plants - Inmaculada Moreno-Alías; Lorenzo León; Raúl de la Rosa; Hava F. Rapoport (Trees, 2009)

Response of waterbirds to alternating clear and turbid water phases in two shallow Mediterranean lakes - Enrique Moreno-Ostos; Mariano Paracuellos; Inmaculada de Vicente; Juan C. Nevado; Luis Cruz-Pizarro (Aquatic Ecology, 2008)

Interannual and between-site variability in the occurrence of clear water phases in two shallow Mediterranean lakes - Enrique Moreno-Ostos; Sergio L. Rodrigues da Silva; Inmaculada de Vicente; Luis Cruz-Pizarro (Aquatic Ecology, 2007)

Low predictability in the dynamics of shallow lakes: Implications for their management and restoration - Inmaculada Vicente; Enrique Moreno-Ostos; Victoria Amores; Francisco Rueda; Luis Cruz-Pizarro (Wetlands, 2006)

Airborne behaviour of Echium pollen - Adolfo Francisco Muñoz Rodríguez; Rafael Tormo Molina; Inmaculada Silva Palacios; Alfonsa Moreno Corchero; Juana Tavira Muñoz (Aerobiologia, 2005)

Thermal structure and energy budget in a small high mountain lake: La Caldera, Sierra Nevada, Spain - Miguel Rodríguez‐Rodríguez; Enrique Moreno‐Ostos; Inmaculada De Vicente; Luis Cruz‐Pizarro; Sergio Luiz Rodrigues Da Silva (New Zealand Journal of Marine and Freshwater Research, 2004)
This work examines the diel change of energy storage and its associated patterns of thermal stratification during the ice‐free period in a high mountain lake (La Caldera Lake, Sierra Nevada, Spain), in response to meteorological conditions. Bihourly data have been implemented to a standard methodology of surface heat exchange calculations in lakes. Strong variations have been observed on the diverse components of the energy budget at different time scales, ranging from diel to seasonal. Additionally, time‐series analyses have been applied to reveal the underlying periodicities involved in relation to the different variables studied. The results obtained from this study provided realistic conditions for the environmental modelling of such processes, which are very sensitive in time scale.